COMPARISON OF VEIN AND CAPILLARY BLOOD SAMPLES ON BLOOD GLUCOSE DURING THE POINT OF CARE TEST (POCT) METHOD IN SANZ MAGNATYA UNIVERSITY HEALTH ANALYSIS STUDENTS - Maria Regina Tri Yonita; Indah Hamida (LPPM Universitas Abdurrab, 2026)
Background: Blood glucose testing can be performed using venous and capillary blood samples and can be measured rapidly using a glucometer as part of Point of Care Testing (POCT). Physiological differences between venous and capillary blood may affect blood glucose measurement results. Objective: This study aimed to compare blood glucose measurement results between venous and capillary blood samples using a glucometer. Methods: This analytical study used a cross-sectional approach and was conducted in April 2026 at the Laboratory of the Health Analyst Department, Sanz Magnatya University. A total of 30 samples were selected using a simple random sampling technique. Data were analyzed using a paired t-test with a significance level of α = 0.05. Results: The mean glucose level in venous blood was 99.70 mg/dL, while the mean glucose level in capillary blood was 91.77 mg/dL. Statistical analysis showed a p-value < 0.001, indicating a statistically significant difference between the two sample types. Conclusion: There was a significant difference in blood glucose measurement results between venous and capillary blood samples using a glucometer. Suggestion: Future studies are recommended to involve larger sample sizes and more specific populations.